Correlation of zinc plasma and IgM anti-PGL-1 levels among close contact of leprosy (Medical Journal of Indonesia, 2012)
Background: Previous study showed leprosy patients have low zinc status. Yet the status of zinc in close-contact, which indicated by IgM anti-PGL1 level, have not determined. The aim of the study was to determine the association of zinc plasma and IgM anti-PGL-1 levels among close contact of leprosy patients in Indonesia. Methods: This was an observational study. Subjects were 186 close-contact leprosy patients. Measurement of zinc plasma status used atomic absorption spectrophotometer while examination of IgM anti-PGL1 level used ELISA (Polyclonal rabbit anti human IgM/HRP/(Dako®). Results: The average level of IgM anti-PGL1 and zinc plasma were 804 unit/mL (± 439.4) and 16.6 μmol/L (± 3.5) consecutively. There was significant correlation between zinc plasma and IgM anti-PGL1 (r = - 0.230; p = 0.002). Conclusion: There is a significant correlation between zinc plasma and IgM anti-PGL1 in close contact of leprosy (Med J Indones. 2012;21:166-9)